Developing design literacy for sustainability : Lower secondary students’ life cycle thinking on their craft-based design products - Maus, Ingvill Gjerdrum (FormAkademisk, 2019)
This article discusses the case study Case Keramikk, examining students’ use of experiential learning from a craft-based design practice in life cycle thinking on their products. Data were constructed through semi-structured group interviews with students of a Norwegian lower secondary school and thematic analysis based on the principles and practices of design for sustainability (DfS). The interview questions engaged the students to assess their practice and products and to estimate environmental considerations. The students used experiential learning that correspond with the DfS practices of eco-efficiency, eco-effectiveness and product durability in the production phase, as well as the distinctive characteristics of materials, products and production decisive for practice of these in the material extraction and use and disposal phases. These reflections enhance students’ development of design literacy for sustainability and strengthen their democratic participation in research for development of education in craft-based design for sustainability.